All Days 1990
DOI: 10.4043/6328-ms
|View full text |Cite
|
Sign up to set email alerts
|

DISCOL: A Long-Term, Large-Scale, Disturbance-Recolonization Experiment in the Abyssal Eastern Tropical South Pacific Ocean

Abstract: A long term, large scale, disturbance decolonization experiment with relevance to the environmental effects of deep-sea mining is described. The study is funded by the West German government and was launched in the abyssal eastern tropical South Pacific Ocean in February-March, 1989. After obtaining pre-impact baseline environmental data, a 10.8 km circular area of seafloor was disturbed using a specially designed "plow-harrow" device. An initial post-impact sampling series was carried out immediately after di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…The DEA is a 10.8 km 2 large circular area (Bluhm, 2001) that was plowed diametrically 78 times in 1989 (Foell et al, 1990(Foell et al, , 1992 to induce a disturbance that would mimic small-scale mining of polymetallic nodules. We deployed newly designed benthic incubation chambers that enabled us to include larger megafauna in pulse-chase studies.…”
Section: Introductionmentioning
confidence: 99%
“…The DEA is a 10.8 km 2 large circular area (Bluhm, 2001) that was plowed diametrically 78 times in 1989 (Foell et al, 1990(Foell et al, , 1992 to induce a disturbance that would mimic small-scale mining of polymetallic nodules. We deployed newly designed benthic incubation chambers that enabled us to include larger megafauna in pulse-chase studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the deep-sea environment such as CIB, the production of sediment organic matter is low (Nath & Mudholkar, 1989) and hence benthic biota has to rely on the particulate organic matter that is produced in the euphotic zone. The benthic community has presumably adapted to the prevailing conditions at deep-sea and any disturbance to their environment will certainly bring major changes in the composition and abundance of benthos (Thistle et al 1985;Foell et al 1990). …”
Section: Introductionmentioning
confidence: 99%
“…The environmental impact studies that have been conducted on nodule ecosystems in the CCZ, the Indian Ocean and the Peru basin (e.g., Amos et al, 1977;Ozturgut et al, 1980;Tilot, 1989;Foell et al, 1990;Thiel et al, 1991Thiel et al, , 2001Bluhm et al, 1995;Fukushima, 1995;Tkatchenko et al, 1996;Radziejewska, 1997;Schriever et al, 1997;Trueblood et al, 1997;Shirayama, 1999;Fukushima et al, 2000;Chung et al, 2001;Oebius et al, 2001;Sharma et al, 2001) mostly focused on alterations to the sediment-nodule interface and impacts to epibenthic faunal communities over very localized areas, compared to the size and the number of areas to be mined. Several reviews (e.g., Smith, 1999;Sharma, 2015;Jones et al, 2017) concluded that there is a lack of information on the potential impact of sediment burial at the scale of the CCZ and that there would be considerable long-term negative effects on the ecosystem.…”
Section: Sedimentation Rates and Mixing Sediment Plumesmentioning
confidence: 99%